For a characterization of the modes of deployment of e-learning courses - QAFAS, Ahlam; KARIM, Hicham; KARIM, Mohamed (Revue Internationale des Sciences de Gestion, 2022)
This text on the characterization of the modes of deployment of e-learning paths follows our literature review on e-learning that we used in our doctoral work. E-learning is defined in this research as a set of multimedia online training methods aimed at specific learning. Practices for deploying e-learning courses to employees have been evolving for several years. The evolution of these practices aims to improve the rate of follow-up by employees of the training content distributed in e-learning as well as their learning. There is an academic and managerial interest in better understanding the factors influencing the act of monitoring e-learning courses by employees as well as on the learning of employees possibly resulting from this monitoring. On the basis of these observations, it is important to propose a characterization of the modes of deployment of e-learning paths among employees. Three main dimensions of the deployment of e-learning in companies have been identified and will be presented in this article: the technological, pedagogical and organizational dimension.